Implementasi Sistem Informasi Inventaris Barang Menggunakan Borland Delphi 7 & Ms. Access 2007 - Bayu Pratama Nugroho; Rudi Hadiyanto (Jurnal Sains Komputer dan Teknologi Informasi, 2019)
In the congregation office of GKE Palangka has not used computerized system, one of them is the management and storage of inventory data of goods. Workers have difficulty managing such a long time in data matching, data retrieval, report generation and presentation, and thus inefficient use of work time. The dominant factor is human error that occurs in processing data and storage and maintenance of paper-shaped documents. The method used is waterfall cycle method which is done through six stages, that is approach systematically and sequence starting from system requirement level then go to phase analysis, design, coding, testing / verification, and maintenance. With the existence of this Information System, the process on the data is done easily, so that the work of the employees in managing inventory data, especially in the field of professional performance asset increases.